1998
DOI: 10.1007/s002130050583
|View full text |Cite
|
Sign up to set email alerts
|

The effect of venlafaxine treatment on the behavioural and neurochemical changes in the olfactory bulbectomised rat

Abstract: In the present study, the effect of chronic treatment with venlafaxine on beta1 and 5-HT2 receptor populations was examined in the frontal cortex of olfactory bulbectomised (OB) and sham operated (SO) animals. The effect of these drugs on the behaviour of the animals on the elevated plus maze and the "open field" was also assessed. Removal of the bulbs resulted in a characteristic increase in locomotor activity in the OB animals in the "open field" which was reversed by chronic venlafaxine treatment. Venlafaxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Contrary to our results, Wieronska et al (2001) reported that OBX rats produced the decreased level of anxiety in the elevated plus maze. Furthermore, it was reported that subchronic treatment with SNRIs venlafaxine reversed the OBX-induced hyperactivity in the open field apparatus, whereas there are no significant effects on the performance in the elevated plus maze (McGrath and Norman 1998). However, we found that milnacipran reversed the performance in the elevated plus maze as well as hyperemotional score in OBX rats.…”
Section: Discussionmentioning
confidence: 51%
“…Contrary to our results, Wieronska et al (2001) reported that OBX rats produced the decreased level of anxiety in the elevated plus maze. Furthermore, it was reported that subchronic treatment with SNRIs venlafaxine reversed the OBX-induced hyperactivity in the open field apparatus, whereas there are no significant effects on the performance in the elevated plus maze (McGrath and Norman 1998). However, we found that milnacipran reversed the performance in the elevated plus maze as well as hyperemotional score in OBX rats.…”
Section: Discussionmentioning
confidence: 51%
“…Neither were abnormalities found in the animals' general health or demeanor. In fact, the doses used in the present study have been demonstrated to be effective in animal models (Stockert et al, 1988;Bodnoff et al, 1989;Malatynska et al, 1995;Ferretti et al, 1995;McGrath and Norman 1998;Gur et al, 2002). Although we have not yet determined the causative factors for this paradox, the dose-related effects of the drugs on the BDNF immunostaining in hippocampal neurons may have functional significance and should be explored further.…”
Section: Discussionmentioning
confidence: 83%
“…It is therefore difficult to determine if SB-269970 has a more rapid onset of action in comparison with these ADs based on this test. To address this issue, we used OBX rats, which require long-term (2-3 weeks) treatment to observe an AD-like response (McGrath and Norman, 1998;Song and Leonard, 2005). An exaggeration of locomotor activity in OBX animals was observed compared with sham rats when placed in a high illuminated open-field ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%